Effect of Combination Folic Acid, Vitamin B6, and Vitamin B12 Supplementation on Fracture Risk in Women: A Randomized, Controlled Trial. (15th December 2017) - Stone, Katie L; Lui, Li‐Yung; Christen, William G; Troen, Aron M; Bauer, Douglas C; Kado, Deborah; Schambach, Christopher; Cummings, Steven R; Manson, JoAnn E
ABSTRACT: Epidemiologic studies have demonstrated an association of elevated plasma homocysteine levels with greater bone resorption and fracture risk. Vitamins B12, B6, and folic acid are cofactors in homocysteine metabolism, and supplementation with B vitamins is effective in lowering homocysteine levels in humans. However, randomized trials of supplemental B vitamins for reduction of fracture risk have been limited. Therefore, we performed an ancillary study to the Women's Antioxidant and Folic Acid Cardiovascular Study (WAFACS), a large randomized trial of women with preexisting cardiovascular disease or three or more coronary risk factors, to test whether a daily B vitamin intervention including folic acid (2.5 mg/day), vitamin B6 (50 mg/day), and vitamin B12 (1 mg/day) reduces nonspine fracture risk over 7.3 years of treatment and follow‐up. Among 4810 women, we confirmed 349 nonspine fracture cases by centralized review of medical records. In a substudy of 300 women (150 in treatment group and 150 controls) with paired plasma samples at randomization and follow‐up (7.3 years later), we measured two bone turnover markers, including C‐terminal cross‐linking telopeptide of type I collagen (CTX) and intact type I procollagen N‐propeptide (P1NP). In Cox proportional hazards models based on intention‐to‐treat, we found no significant effects of B vitamin supplementation on nonspine fracture risk (relative hazard = 1.08; 95% confidence interval, 0.88 to 1.34). In a nested case‐cohort analysis, there were no significant effects of B vitamins on fracture risk among women with elevated plasma homocysteine levels, or low levels of vitamins B12 or B6, or folate at baseline. Furthermore, treatment with B vitamins had no effect on change in markers of bone turnover. We found no evidence that daily supplementation with B vitamins reduces fracture risk or rates of bone metabolism in middle‐aged and older women at high risk of cardiovascular disease. © 2017 American Society for Bone and Mineral Research.